INOVASI PROGRAM BERIKAN PELAYANAN KHUSUS TERPADU ADMINISTRASI KEPENDUDUKAN (BESUTAN) OLEH DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN JOMBANG - Ivana, Nabilah; Meirinawati, Meirinawati (Universitas Negeri Surabaya, 2023)
Besutan Innovation (Provide Special Integrated Population Administration Services) is an innovation by the Jombang Regency Population and Civil Registration Service by providing population administration services with a pick-up system, especially for managing KK and electronic-KTP documents. This service was created to make it easier for people with special needs due to physical and mental disabilities, as well as old people and chronically ill people to be able to obtain residence rights as citizens.The type of research used is descriptive research with qualitative methods. The focus of this study uses the theory of innovation capability components according to Emery et al., (2016: 14-31), namely 1) innovative culture, 2 ) leadership, 3) expert knowledge, 4) stakeholder engagement, 5) innovative work design. Data collection techniques used using observation, interviews, and documentation. The analysis technique used consists of data collection, data reduction, data presentation, and drawing conclusions.The results of the study show that the implementation of Made Innovation has been going quite well and includes the five components of innovation capability even though there are still some obstacles in its implementation. Innovative culture has been implemented in daily activities. Leadership has a great sense of responsibility and is able to coordinate its employees. Expert knowledge is sufficient and qualified to carry out their duties and there are no significant difficulties. Stakeholder involvement shows that all parties play an active role and support the Besutan program. Innovative work designs that are applied flexibly and make it easier for people with physical and mental limitations.